Albumin-Related Inflammatory Indices in the Prediction of Placental Abruption: A Clinical-Laboratory Study - Bayrak, Ayse Cigdem; Sarikaya Kurt, Dilara; Seyhan, Berna; Yakut Yucel, Kadriye (Gynecology Obstetrics & Reproductive Medicine, 2025)
Objective: We aimed to evaluate the diagnostic utility of albumin-related inflammatory indices in predicting placental abruption (PA) and to explore their potential advantages over conventional clinical and laboratory parameters. For this purpose, we assessed the neutrophil-to-albumin ratio (NAR), neutrophil percentage-to-albumin ratio (NPAR), blood urea nitrogen-to-albumin ratio (BAR), and serum albumin-to-creatinine ratio (sACR), and examined their associations with neonatal outcomes. Study Design: This retrospective cohort study included 179 singleton pregnancies, comprising 64 patients diagnosed with PA and 115 healthy controls. Maternal demographic and clinical characteristics were recorded, including age, gravidity, parity, pre-pregnancy body mass index (BMI, kg/m²), history of preterm birth, previous cesarean delivery, use of low-molecular-weight heparin (LMWH), need for blood transfusion, and length of hospital stay. Neonatal outcomes included gestational age at birth, birth weight, 1- and 5-minute Apgar scores below 7, and neonatal intensive care unit (NICU) admission. Receiver operating characteristic (ROC) curve analysis was used to evaluate the diagnostic performance of the indices, while multivariate logistic regression and analysis of covariance (ANCOVA) were performed to adjust for gestational age. Results: NPAR and BAR levels were significantly higher in the PA group compared to controls. These indices demonstrated moderate discriminatory ability and remained statistically significant after adjustment for gestational age. Although NAR and sACR were also associated with PA, their diagnostic utility appeared more limited. Conclusion: Among the albumin-associated inflammatory indices evaluated, NPAR and BAR demonstrated the strongest associations with placental abruption and may serve as useful adjunctive markers in clinical evaluation. Although NAR and sACR also showed statistically significant associations, their limited diagnostic performance suggests the need for further investigation before clinical implementation.